Sharks & minnows - Pumphrey, Jarrett (Pumphrey, Jarrett. Link and Hud, 2025)
"Lincoln and Hudson Dupre̓ are ready for their summer holiday at the coast. The ocean is perfect for their imagined escapades, but when their dad cuts their trip short, it seems like the end of Link and Hud's aquatic adventures until they run into the ultra-competitive Donaldson brothers, who are on the local swimming team. The Sharks and Coach Strickler will do anything to win and they're not particularly welcoming. Well, if Link and Hud can't join the Sharks, they'll set up their own swimming team, with events like deep-sea treasure hunting and supersonic water walking. When Coach Strickler tries to shut down their team, Link and Hud and their Mighty Minnows must outswim and outsmart the Sharks to keep the fun afloat. With warm and authentic humour, real-life brothers Jarrett and Jerome Pumphrey have blended prose and graphic novel style illustrations to craft a unique and subversive new series." --